Funeral Practice of the Sapalli Culture in the Reflection of Vedic Texts - Kasparov Armen R. (Поволжская археология, 2023)
Northern Bactria in the Bronze Age became the arena of complex processes of interaction between the local population and the world of the Eurasian steppes. During this period, the early urban agricultural Sapalli culture, where the contacts of the two traditions were reflected not only in material but also in spiritual culture, developed and functioned on the territory of the south of modern Uzbekistan. Based on the results of studies of the burial grounds of Bustan VI–VII, the first-time attempt to verify the funeral rite with the written sources of the ancient Indo-Aryans and Indo-Iranians was made in the present work. The chosen approach made it possible to solve simultaneously several problems: to clarify the path of advancement of the Indo-Aryan tribes to India; trace one of the ideological foundations of the formation of the Bactrian civilization; illustrate the impact on the local environment of the steppe ethnos represented by the Andronovo population, identified with the Indo-Aryans. The results of the realized work allow us to speak about the significant presence of the Aryan tradition in Sapalli society and the emergence of new forms of funeral rituals. The changed mythological and ritual statements in cosmogonic representations have established as their main constant the maintenance of universal balance and order, carried out through a system of sacrifices, the highest of which at the final stage of life was a person.